Índice de manejo de carbono em solos cultivados no agropólo Mossoró-Assu - Lima, Rebeca Nairony da Silva (Universidade Federal Rural do Semi-Árido, 2017)
One of the main production areas of irrigated and rainfed agriculture of potiguar semiarid it is insert in the agropólo Mossoró-Assu, due to diversification of physical, chemical and mineralogical characteristics that the soils of this area presents. Currently, be few surveys on the management applied in such areas and its influence in soil quality. A practical assessment witch may indicate the behavior of soil organic matter in managed areas and indicate the current quality is the same is the use of Carbon Management Index. With this, the objective of this study was evaluate behavior of organic matter, as well as its lability estimating the carbon management index in areas with different uses in Agropólo Mossoró-Assu. The studied areas are inserted in municipalities that compose the Agropólo, with different uses, being these located in Serra do Mel under cashew cultivation; Apodi/RN, in a consortium area between maize and beans, and a second area intercropped with fruit; Baraúna/RN, managed with melon e, Governador Dix-Sept Rosado, under maize cultivation. Were collected in each area five samples composed of soil, evenly distributed in the area, in depths of 0 – 10 cm and 10 – 20 cm, and adjacent native forest areas used as reference. Were realized chemical analyzes of pH in water, electric conductivity (EC), available phosphorus (P), total organic carbon (TOC) and labile carbon (LC), being estimated the carbon management index (BMI) of the areas in use. The cultivated area with melon presented the highest mean levels of P, was well was of EC, certainly due to the management applied in the area, with use of fertigation over 15 years, opposing the area managed with beans under organic fertilization, which presented the lowest values of EC. For pH there are values that tend to acidity in the area planted with cashew and alkalinity in the intercropped area with maize and beans and the other areas tend to neutrality. The highest level of TOC (27,4 g/kg in 0 -10 cm e 27,0 g/kg in 10-20 cm) e LC (1,7 g/kg in 0-10 cm e 1,9 in 10-20 cm) were found in the area managed with melon. None of the areas studied presented BMI closed to the values of the areas used as reference, thus indicating management that tend to degrade of soil organic matter, needing more sustainable practices. However, the area present highest BMC, among the managed areas, was the area on cultivation of melon, followed by areas with maize e intercropped area with maize/beans, with values of BMC varying from 30 to 51, between areas and depths.
Monografia
Keywords: Matéria orgânica do solo; Semiárido; Labilidade do carbono; Soil organic matter; Semiarid; Carbon lability; CIENCIAS AGRARIAS::AGRONOMIA